Comparison of Ardabil people's utilization of national media and satellite networks in receiving news - Baratchian, Taher (2020)
Virtual social networks nowadays play a very important role in getting and receiving daily news. Therefore, it is necessary to know the extent and reasons for users to use this tool and compare it with other media. Therefore, it is essential to know the extent and reasons for users to utilize this tool and compare it with other media. This study aimed to investigate the comparison of the use of Ardebil people from social networks and other media in receiving the news. In this descriptive-inferential study 400 Ardabil people were randomly selected. The validity and reliability of the questionnaire developed by the researcher were obtained and completed by the participants. The data were then analyzed using SPSS software. Research findings show that participants prefer to gain news from social networks to other media and most of them think that using social media has been able to reduce the utilization of other media. The findings show that the use of social media in news coverage has somewhat reduced the amount of time spent watching television and satellite. The reasons for this media shift in news acquisition include the social networking content attractiveness in the indicators of accuracy and transparency, the speed of dissemination, the neutrality of news, the latest visual reports, the visual and auditory attractions, the attention to quality of programs, attention to Respondents cited low censorship, addressing issues of interest to audiences, using news images, and using expert view of other media as sources of news. The participants also believed that social networks have a low level of censorship and news silence. Since the national media should be the most important medium in getting the news to a community, as an emerging media social networks have been able to take deep root in human life. These networks have positive features, but on the other hand, they have problems that need special attention.